2017
DOI: 10.1002/app.45874
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and simulated investigation of temperature distribution of UHMWPE laminated composites during hot pressing process

Abstract: In this article, the influence of molding temperature on the mechanical properties and ballistic impact behavior of the ultrahigh molecular weight polyethylene (UHMWPE) laminated composites has been investigated. The results demonstrate that with the temperature increasing from 80 to 120 °C, the tensile strength decreases while the interlaminar bonding strength increases. The UHMWPE laminated composites manufactured by hot pressing of 75 layers UHMWPE fabrics show excellent ballistic performance when the moldi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Zeng [ 35 ] found that as the temperature increased from 80 to 120 °C, the tensile strength decreased while the interlaminar bonding strength increased. Comparing Zeng's findings with the results of this study, it is evident that the influence of temperature on in‐plane tensile strength and interlaminar bonding strengths can be modified by using different ranges of molding temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Zeng [ 35 ] found that as the temperature increased from 80 to 120 °C, the tensile strength decreased while the interlaminar bonding strength increased. Comparing Zeng's findings with the results of this study, it is evident that the influence of temperature on in‐plane tensile strength and interlaminar bonding strengths can be modified by using different ranges of molding temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Cao et al [ 14 ] evaluated the effect of temperature on the ballistic performance of UHMWPE laminates, noting differences in deformation processes, failure characteristics, and penetration depths across a temperature range from −20 to 95 °C. Zeng et al [ 15 ] reported a decrease in tensile strength and an increase in interface bonding strength with rising hot-pressing temperatures. Zheng et al [ 16 ] assessed the influence of pressure and temperature on the interface bonding strength of UHMWPE fiber/styrene-butadiene-styrene resin composites through T-peel tests, finding a more pronounced effect of pressure over temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, because the drilling process of the UHMWPE composite has not been analysed adequately for materials manufactured using hot-pressing technology, which is a common method for manufacturing protective elements against impacts [29,30], it is necessary to carry out a more in-depth study. Thus, this paper focuses on the study of the drilling process of UHMWPE composite materials manufactured by means of hot-pressing technology.…”
Section: Introductionmentioning
confidence: 99%